Influence of flute number and stepped bit geometry when drilling CFRP/Ti6Al4V stacks. (March 2019) - Alonso, Unai; Calamaz, Madalina; Girot, Franck; Iriondo, Edurne
Abstract: Hybrid stacks made of carbon reinforced plastic (CFRP) and Ti-6Al-4 V alloy (Ti) are often drilled together to reduce positional errors, enhance tight tolerances and minimize machining time. However, this is a complex task due to the dissimilar properties of each material. Tool geometry has a significant impact on the machinability of CFRP/Ti stacks. In this study, the influence of flute number and stepped bit design was experimentally investigated. Confocal and SEM microscopy were used to analyse the evolution of the cutting-edge micro-geometry and the dominant wear modes. The results have shown that a stepped design with three flutes leads to a slower wear progression, lower cutting forces and less hole damage. Furthermore, this paper also highlights the influence of the geometrical characteristics of the stepped tool design on the drilling stage number and on the shape of the thrust force signal. The information gathered can be used for the improvement of the process competitiveness in terms of the reduction of production time and cost.